Elementy romanistyczne w prawie karnym Polski przedrozbiorowej - Sondel, Janusz (Prawo Kanoniczne, 1994)
The analysis of Polish penal law sources allows to state that the influence of Roman law can be noticed also in this branch of law. Its direct application can also be observed in the Middle Ages and in the centuries that followed. The Cracow Academy Erection Act and the Priviledge of the City of Cracow, both dated May 12th, 1364, ordered that every lay scholar, bedel, stationarius etc., who was accused of serious crimes, should be responsible before the king’s court iuxta leges, that is according to Roman law. The rule was restated several times and it shows a surprising vitality, as it not only survived in Poland of the Nobility Republic but was invoked in the eighteenth century as well. Roman law was also applied in two famous crimen laesae maiestatis casas in 1620 and 1773. During the proceedings, their participants cited Justinian's collections several times when they perceived a lack of domestic regulation. The courts called upon the collections in certain degree in both cases. Urban law gives numerous examples in this area of studies. For years, the law was considered the domain of Roman law influence in Poland. The writings of Bartłomiej Groicki, who lived in the sixteenth century, broadly relate the crimen laesae maiestatis and they contain various direct appleals to Roman law (C. de feriis L. Provinciarum praesides, lex lulia de adulterii coercendis, lex Attinia, lex India et Płatnia, lex X II Tabularum etc.) which create a basis for his ample deliberation. It seems that the most interesting discussion concerns the typical for Roman law penalty for patricides (poena cullei). Its reception into Polish urban law had occurred through Speculum Saxonum and it constitutes a strong evidence for the influence of the Roman law system on penal legislation.